RELATIONSHIP BETWEEN THE FACTORS AFFECTING EXERCISE BEHAVIOR AND PHYSICAL FITNESS AMONG UNIVERSITY STUDENTS - Aungkana Boonsem; Anan Malarat; Sathin Prachanban (Journal of Physical Education)
ABSTRACT This research used causal research design to study the relationship of the various factors and exercise behaviors affecting the physical fitness of university students based on the PRECEDE FRAMEWORK. The objectives included the following: (1) to compare the personal factors that influenced exercise behavior; (2) to study the relationship between the predisposing, enabling and reinforcing factors; and exercise behaviors; and (3) to compare the level of exercise behavior affecting physical fitness. The sample group were simple random sampling. This research consisted of the questionnaire and physical fitness test of five items on the Body Mass Index, Sit and Reach, Hand Grip Strength,60 Second Chair Stand and 3-Minute Step Up and Down. The data were analyzed using an independent t-test, One-Way ANOVA, One-Way ANCOVA and Multiple Regression Analysis, with a statistically significant level of 0.05. The results showed that gender affected exercise practices of university students, and with no impact on knowledge and attitudes, while age affected exercise practice by controlled gender. The predisposing, enabling and reinforcing factors in the PRECEDE FRAMEWORK concept had a positive effect on exercise behavior by promoting the exercise behaviors of university students that have been continuously implemented and caused students to change their physical fitness and improve all aspects of its. In addition, exercise behavior of knowledge and attitudes to exercise had no effect on physical fitness, whlie exercise behavior of attitude and the factors of predisposting, enabling and reinforcing affected the practice behavior of male students.